2021
DOI: 10.1021/acs.langmuir.1c01941
|View full text |Cite
|
Sign up to set email alerts
|

Atomic, Molecular and Hybrid Oxygen Structures on Silver

Abstract: Interactions between oxygen and silver are important in many areas of science and technology, including materials science, medical, biomedical and environmental applications, spectroscopy, photonics, and physics. In the chemical industry, identification of oxygen structures on Ag catalysts is important in the development of environmentally friendly and sustainable technologies that utilize gas-phase oxygen as the oxidizing reagent without generating byproducts. Gas-phase oxygen adsorbs on Ag atomically by brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 56 publications
(99 reference statements)
2
31
0
Order By: Relevance
“…Although similar vibrations were also found in 4-fold sites of nonreconstructed metallic surfaces (Figure S3b,c) of more open facets such as Ag(110) and Ag(100), ab initio atomistic thermodynamic phase diagram studies show that oxidic reconstructions of the Ag(111) and Ag(110) facets are more stable in comparison to their nonreconstructed metallic counterparts under reaction conditions that are relevant to ethylene oxidation. The vibration range of calculated Ag 4 –O 2 species (700–800 cm –1 ) exhibits good agreement with the hybrid oxygen species (600–810 cm –1 ) reported in the recent literature . In comparing the binding energies with the vibrational frequencies of the surface O* and O 2 * species on both oxygen reconstructed and pristine metallic facets (Figure S4), an intuitive general trend is observed.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…Although similar vibrations were also found in 4-fold sites of nonreconstructed metallic surfaces (Figure S3b,c) of more open facets such as Ag(110) and Ag(100), ab initio atomistic thermodynamic phase diagram studies show that oxidic reconstructions of the Ag(111) and Ag(110) facets are more stable in comparison to their nonreconstructed metallic counterparts under reaction conditions that are relevant to ethylene oxidation. The vibration range of calculated Ag 4 –O 2 species (700–800 cm –1 ) exhibits good agreement with the hybrid oxygen species (600–810 cm –1 ) reported in the recent literature . In comparing the binding energies with the vibrational frequencies of the surface O* and O 2 * species on both oxygen reconstructed and pristine metallic facets (Figure S4), an intuitive general trend is observed.…”
supporting
confidence: 63%
“…The oxygen species on/in Ag were also detected with in situ Raman spectroscopy. Their assignments have been speculated to be Ag 3 O (300 cm –1 ), Ag–O bulk (630 cm –1 ), Ag–(O–O) 2– (697 cm –1 ), subsurface Ag–O (802 cm –1 ), AgO (956 cm –1 ), and molecular Ag–O 2 (1053, 1078, 1286 cm –1 ). , In addition to surface oxygen species, subsurface oxygen is also believed to strongly influence the catalytic properties of Ag. , A consensus on the oxidation state of silver and nature of the oxygen species and their reactivity, however, has not been reached to date. In this context, density functional theory (DFT) calculations can potentially map Raman spectroscopy bands for the O–Ag system with plausible surface and adsorbate structures. ,, Recent studies showed examples of such an approach, in which hybrid surface–subsurface O 2 * species on fully (Ag 2 O­(001)) or partially oxidized Ag surfaces (the p(4 × 4) oxidic reconstruction of Ag(111)) were found to exhibit vibrational frequencies between 600 and 840 cm –1 . , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar cluster and periodic structure models were previously successfully used to describe oxygen, H 2 O 2 and OOH adsorption on Au and other adsorbates on multiple surfaces. 9,13,15,18–28 The calculations show that on most Au surfaces hydroxyls preferentially adsorb on a bridge Au–Au site, with ν (O–H) being in a narrow range from 3683 to 3687 cm −1 (Fig. 2).…”
mentioning
confidence: 98%
“…The positions of the Pt atoms in the bottom two layers were constrained, simulating the bulk structure of Pt nanoparticles. Similar computational settings were previously used for studying adsorption and reactivity on multiple metallic catalytic surfaces. ,, …”
Section: Experimental and Computational Methodsmentioning
confidence: 99%